Immersive Anatomy Atlas—Empirical Study Investigating the Usability of a Virtual Reality Environment as a Learning Tool for Anatomy - Weyhe, Dirk; Uslar, Verena; Weyhe, Felix; Kaluschke, Maximilian; Zachmann, Gabriel (Frontiers in Surgery, 2018)
We developed a prototype of a virtual, immersive and interactive anatomy atlas for surgical anatomical training. The aim of this study was to test the usability of the VR anatomy atlas and to measure differences in knowledge acquirement between an immersive content delivery medium and conventional learning (OB). Twenty-eight students of the 11th grade of two german high schools randomly divided into two groups. One group used conventional anatomy books and charts whereas the other group used the VR Anatomy Atlas to answer nine anatomy questions. Error rate, duration for answering the individual questions, satisfaction with the teaching unit, and existence of a medical career wish were evaluated as a function of the learning method. The error rate was the same for both schools and between both teaching aids (VR: 34.2 %; OB: 34.1 %). The answering speed for correctly answered questions in the OB group was approx. twice as high as for the VR group (mean value OB: 98 sec, range: 2-410 sec; VR: 50 sec, 1-290 sec). There was a significant difference between the students of the two schools based on a longer processing time in the OB condition in School B (mean OB in School A: 158 sec; OB in School B: 77 sec). The subjective survey on the learning methods showed a significantly better satisfaction for VR (p = .012). Medical career aspirations have been strengthened with VR, while interest of the OB group in such a career tended to decline. The immersive anatomy atlas helped to actively and intuitively perform targeted actions that led to correct answers in a shorter amount of time, even without prior knowledge of VR and anatomy. With the OB method, orientation difficulties and/or the technical effort in the handling of the topographical anatomy atlas seem to lead to a significantly longer response time, especially if the students are not specially trained in literature research in books or texts. This seems to indicate that the VR environment in the sense of constructivist learning might be a more intuitive and effective way to acquire knowledge than from books.